Business Intelligence of MSMEs Boarding Houses, and Their Sustainability (Case Study of Boarding Houses in South Tangerang City) - Zul Asman; Adler Haymans Manurung (Dinasti Publisher, 2023)
This study discusses efforts to maintain the business continuity of MSME actors through a literature study on regulations and publication data related to MSME. Descriptive qualitative methods are used to analyze the steps needed by SMEs to maintain their existence. The data used is secondary data in the form of official reports and publications from related parties regarding turnover, income, and government support for MSMEs. The results of the study show that government policy support alone is not enough, the active role of all components of MSME actors is also needed. The government can maximize socialization with the help of local governments so that assistance can be received properly. In addition, MSME actors also play a role in making changes both in terms of production innovation, technology utilization, and marketing through digitization to maintain the continuity of their business. time